Greening the City, Cultivating Community - Blanc, Nathalie; Dessein, Joost; Freitas, Raquel; Soini, Katriina; Cadarso, Maria; Fairclough, Graham; Hristova, Svetlana; Horlings, Lummina; Lang, Marion; Chiarini, Roberta; Cudlínová, Eva; Reimer, Mario (Jyväskylä University Press, 2015)
Since the publication of the Brundtland Report and Agenda 21, interest in urban nature has grown, and for social, cultural as well as environmental reasons. For many decades, nature within cities has been ‘civilised’, relegated to a decorative role, and appreciated at best for relaxation and recreation. This position has been challenged by recent enthusiasm for community gardening and the more radical ‘guerrilla gardening’. These activities reflect on the place and role of inhabitants’ engagement with nature in the context of urbanisation.
Keywords: Greening; City; Cultivation; Community